Effects of high-altitude environments on intervertebral disc degeneration and transcriptome profiling of the nucleus pulposus - Fu, Jiawei; Tang, Rong; Ran, Tianfei; Zhou, Yue; Huang, Bo (Frontiers in Cell and Developmental Biology, 2025)
BackgroundLow back pain (LBP) is a leading cause of disability in elderly individuals, and intervertebral disc degeneration (IDD) is the major contributor to LBP. Aging is an important factor contributing to IDD. Research has indicated that the incidence of lumbar intervertebral disc protrusion is significantly greater in high-altitude areas. However, the effects of a high-altitude environment on IDD and the underlying mechanism remain unclear.MethodsWe identified changes in the intervertebral discs of rats of different ages in a simulated high-altitude, low-pressure, and hypoxic environment. Furthermore, through transcriptome analysis, we investigated genes that are differentially expressed during intervertebral disc aging and degeneration at different altitudes.ResultsGene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses revealed that biological processes and cellular senescence are important molecular events and regulatory pathways for the development of IDD in individuals who live in high-altitude environments. In the transcriptome sequencing of rat intervertebral discs with aging and degeneration at different altitudes, the results of the GO and KEGG analyses revealed that cell cycle arrest is a key factor in aging and degeneration. In addition, through overlap analysis, we observed changes in SFN expression in high-altitude environments, and this change may be meaningful.ConclusionOur findings clarify the effects of high altitude on disc degeneration and predict potential molecular targets that can be used to identify or intervene in disc degeneration caused by high altitude by mining the common features of NP cells associated with the aging process in HA environments through transcriptome sequencing.